Connection between central bank balance sheets and stock market valuations - Aspinmaa, Ellinoora (2021)
The aim of the current thesis is to study one of the unconventional monetary policy instruments, asset purchase programs and their impact on another central bank’s balance sheet developments and stock index returns. This thesis focuses on three central banks, the Federal Reserve from the United States, the European Central Bank and the Bank of Japan. Three stock indices are also selected from the corresponding areas: Standard & Poor’s 500, EURO STOXX 50 and Nikkei 225. The time period covered in the current thesis extends from December 2002 until 2020, and the method chosen is VAR-analysis. The results indicate that whereas the stock index returns are strongly connected to each other, the connections between central bank balance sheet extensions and stock index returns are relatively vague. The study of the three central banks suggests that while the central banks make their own decisions related to balance sheet activities and purchase programs independently, a cointegration relationship is found among central banks’ balance sheets studied, indicating that these decisions tend to be similar to the decisions made by other central banks especially in the long-run perspective.